Alih Kode dan Campur Kode dalam Keluarga Bapak Misja Di Karawang - Julaeha Julaeha; Sinta Rosalina (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to understand the practice of code switching or code mixing between Sundanese and Indonesian at home in Panyingkiran village region in Karawang. By using a qualitative approach, this research explores the motivation, understanding, function, impact, and tendency to use code switching in bilingual households. Research methods include in-depth interviews with family members who have experienced the use of code-switching, direct observation of everyday conversations in the family, and analysis of the context in which code-switching is used in the family. The research participants consisted of five families who were deliberately selected based on the inclusion criteria. The results of the research show that code-switching from Sundanese to Indonesian is a common practice at home in Panyingkiran village in Karawang. The motivation for using code-switching includes efforts to integrate cultural and family identity, express feelings, and convey meaning better. The use of code-switching also reflects the trend of cross-generational change, with Bahasa Indonesia increasingly dominating everyday family conversation. Although code switching is considered normal and socially acceptable at home, the continuous mastery of Sundanese and Bahasa Indonesia can have an impact on children's language skills. Children often experience difficulties in developing their Sundanese language skills and dominate the use of Indonesian. This study contributes to the understanding of the practice of code switching from Sundanese to Indonesian at home in Panyingkiran village region in Karawang. The implications of this research may have implications for the development of language education policies, as well as for a better understanding of the role of language in shaping cultural identity and family relationships in multilingual settings.